2001
DOI: 10.1055/s-2001-16488
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic and Neuroprotective Actions of Ginsenosides Rb1 and Rg1

Abstract: The ginsenosides have many pharmacological actions, including various actions on the nervous system. Our previous studies have demonstrated that two ginsenosides, Rb(1) and Rg(1) improve performance in a passive avoidance-learning paradigm and enhance cholinergic metabolism. The present study was designed to examine the cellular neurotrophic and neuroprotective actions of two pure ginsenosides in two model systems. PC12 cells were grown in the absence or presence of nerve growth factor (NGF) as a positive cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(80 citation statements)
references
References 0 publications
3
75
0
Order By: Relevance
“…Ginseng may also reverse the neurotoxic effects of MPP + through elevation of NGF mRNA expression (21). In accordance, Salim et al (35) showed that ginsenosides Rb1 and Rg1 elevate NGF mRNA expression in rat brain and Rudakewich et al (36) concluded that both ginsenosides potentiate NGFinduced neurite outgrowth in cell culture. Furthermore, it has been reported that ginsenosides Rb1, Rg1, Rc, and Re inhibited tyrosine hydroxylase activity and exhibited anti-dopaminergic action since they reduced the availability of dopamine at presynaptic dopamine receptors (37).…”
Section: Ginseng's Role In Parkinson's Disease Modelssupporting
confidence: 57%
“…Ginseng may also reverse the neurotoxic effects of MPP + through elevation of NGF mRNA expression (21). In accordance, Salim et al (35) showed that ginsenosides Rb1 and Rg1 elevate NGF mRNA expression in rat brain and Rudakewich et al (36) concluded that both ginsenosides potentiate NGFinduced neurite outgrowth in cell culture. Furthermore, it has been reported that ginsenosides Rb1, Rg1, Rc, and Re inhibited tyrosine hydroxylase activity and exhibited anti-dopaminergic action since they reduced the availability of dopamine at presynaptic dopamine receptors (37).…”
Section: Ginseng's Role In Parkinson's Disease Modelssupporting
confidence: 57%
“…Ginseng may also reverse the neurotoxic effects of MPP + through elevation of NGF mRNA expression 44) . In accordance, Salim et al 58) showed that ginsenosides Rb 1 and Rg 1 elevate NGF mRNA expression in rat brain and Rudakewich et al 59) concluded that both ginsenosides potentiate NGF-induced neurite outgrowth in cell culture. Ginsenosides Rb 1 , Rg 1 , Rc and Re inhibited tyrosine hydroxylase activity and exhibited antidopaminergic action since they reduced the availability of dopamine at presynaptic dopamine receptors 60) .…”
Section: Ginseng's Role In Parkinson's Disease Modelsmentioning
confidence: 55%
“…They also increase choline acetyltransferase levels in rodent brains 72) . Such data indicate that these compounds may improve central cholinergic function in humans and may be used to treat memory deficits 59) . Ginsenosides increased dopamine and norepinephrine in cerebral cortex 59) which may explain the favorable effects of ginseng extract upon attention, cognitive processing, integrated sensory-motor function and auditory reaction time in healthy subjects 73,74) .…”
Section: Effect On Neurotransmitter Changes By Ginsenosidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In that context, many studies have shown that ginseng and ginseng products protect cells from a variety of insults. In vitro, ginsenosides treatment was demonstrated to increase survival and promote neurite growth in dopaminergic cells (Radad et al, 2004b), increase neurite growth in the presence of sub-optimal doses of Nerve Growth Factor (NGF) (Rudakewich et al, 2001), protect against PCB 52 induced apoptotic cell death (Lee et al, 2004), protect cells against glutamate toxicity (Radad et al, 2004a) and against ultraviolet-B induced apoptosis (Lee et al, 2003). In vivo, ginsenosides treatment was shown to reduce hypoxic brain injury in rats (Park et al, 2004), improve recovery in a model of ischemic brain injury (Park et al, 2004) and in a model of traumatic brain injury (Ji et al, 2005), protect against toxic interventions in two models of Parkinson disease (Van Kampen et al, 2003) and against methamphetamine toxicity (Wu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%